Asuhan Kesehatan Gigi Dan Mulut Pada Pasien Tn.Tm (15 Thn) Dengan Kasus Karies Gigi Mencapai Pulpa (Politeknik Kesehatan Kemenkes Bandung, 2020)
Dental caries or cavities is a disease of hard tooth tissue marked by damaged enamel and dentin caused by bacterial metabolism in plaque. The result of untreated caries will cause the cavities to become larger and deeper, and eventually will cause the teeth to die.The tooth that has died will produce gas derived from the metabolism of microorganisms, the gas will cause unpleasant odors. Halitosis is a general term used to describe bad breath originating from both the oral cavity and outside the oral cavity.The purpose of this study was to obtain a picture of dental and oral health care in respondents aged 15 years with a case of caries reaching the pulp. The research data is presented with the concept of dental and oral health care consisting of the process of assessment, diagnosis, planning, implementation, and evaluation. Dental and oral health care that has been done, there are 3 basic human needs on the client that are not fulfilled, namely not fulfilling a healthy facial impression due to halitosis, not fulfilling the need for the function and biological condition of good teeth because they have caries reaching the pulp and responsibility responsible for oral health due to lack of responsibility for oral health. The evaluation results show that there are 2 human needs on the client have been met again and 1 basic human needs only partially met.